2022
DOI: 10.1590/fst.117121
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A (HSYA) improve scars by vivo and vitro study

Abstract: The purpose of this research was to evaluate HSYA' effects and mechanisms to improve Scars Induced by Anticoagulant Injection by vivo and vitro study. New Zealand rabbits were divided into Normal control (NC), Anticoagulant, Anticoagulant+HSYA-Low, Anticoagulant+HSYA-Middle and Anticoagulant+HSYA-High. Measuring TGF-β1 and IL-1β concentration by Elisa assay; evaluating pathology and fibrosis level by HE and Masson staining, measuring collage I, collage III, TLR4 and NF-κB(p65) protein expression by IHC assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Studies have shown that both the polysaccharide and alcohol extracts of SS have inhibitory effects on the activity of XO to some extent, and the alcohol extract of SS has better UA-lowering ability than the crude polysaccharide of SS. The polysaccharide of SS showed an anti-competitive inhibition effect, whereas the alcohol extract showed non-competitive inhibition when interacting with XO ( Li et al, 2022a ).…”
Section: Treatment Of Hua With Tcmmentioning
confidence: 99%
“…Studies have shown that both the polysaccharide and alcohol extracts of SS have inhibitory effects on the activity of XO to some extent, and the alcohol extract of SS has better UA-lowering ability than the crude polysaccharide of SS. The polysaccharide of SS showed an anti-competitive inhibition effect, whereas the alcohol extract showed non-competitive inhibition when interacting with XO ( Li et al, 2022a ).…”
Section: Treatment Of Hua With Tcmmentioning
confidence: 99%